Ornamentation and Transformations Of Architectural facades In Different Architectural Periods - Abdulahaad, Enas Salim; Almaamouri, Abdullah Saadoon Salman (Iraqi Journal of Architecture and Planning, 2018)
Ornamentation emerged as one of the most prominent concepts that associated with the architecture for its final crystallization through creation and production together, which drew the attention of research concept, after clarifying the depth of the Ornamentation in the architectural surfaces as a system of intellectual and material oriented to the architectural output and as a transient over time and confirmed transformations of models of adornment, The research objective is to explore the indicators of ornamentation that responsible for the formulation and embodiment of architectural products according to the .transformations of architectural visions The research adopted descriptive analytical method for the architectural surfaces ornament in the different periods and currents, that showed the transformations of ornament which make deep surfaces by the relation (inout) or (structure-skin) after showing the effectiveness of the transformation in each era of them to reach the conclusions of the research The design of the architectural surfaces in their transformations on the indicators of intellectual ornamentation represented by semantic concepts and values, and physical indicators represented by the formal characteristics and properties of the material to produce different patterns of ornamentation which used by the designer to control the fundamental relationship of the deep architectural surfaces (in- out) through the interweaving of (structure - skin) in varied possibilities as research confirmed through its methodology.